Effects of metabolic and organ function factors on the efficacy of radioactive iodine therapy for hyperthyroidism - Hu, Yue; Liu, Shan; Xiong, Xiaoliang; Wang, Lixing; Zhao, Yinlong (Frontiers in Endocrinology, 2025)
IntroductionRecent studies suggest that metabolic and organ function indicators could influence radioactive iodine treatment (RAIT) efficacy in hyperthyroid patients, but their relationships with thyroid function remain unclear.ObjectiveThis study aims to explore the impact of these markers on RAIT efficacy and thyroid function.MethodA total of 135 hyperthyroid patients undergoing RAIT were enrolled, with biomarkers collected at baseline and 1, 3, and 6 months posttreatment. These included thyrotropin receptor antibody (TRAb), free triiodothyronine (FT3), free thyroxine (FT4), thyroid-stimulating hormone (TSH), urinary iodine concentration (UIC), serum iodine concentration (SIC), 25-hydroxyvitamin D, alanine aminotransferase, aspartate aminotransferase, and serum creatinine (Scr). We mainly focus on the outcomes of the impact of metabolic and organ function markers on RAIT efficacy and their correlation with changes in thyroid function.ResultsLogistic regression identified age as a predictor of RAIT efficacy (OR = 0.957, p = 0.025), with older patients less likely to achieve clinical improvement. Scr showed borderline significance (p = 0.049). Early after treatment, SIC was positively correlated with TSH (r = 0.204, p = 0.018), whereas UIC and SIC were significantly negatively correlated with TSH at 6 months during treatment (p < 0.05). In addition, higher Scr levels were consistently and significantly associated with lower FT3 and FT4 and higher TSH at multiple time points (p < 0.05).ConclusionAge was a relative factor influencing RAIT efficacy, while iodine nutritional status exhibited dynamic, time-dependent effects on TRAb and TSH. Elevated Scr promotes reductions in FT3 and FT4 and an increase in TSH.